2016
DOI: 10.1007/s11121-016-0651-6
|View full text |Cite
|
Sign up to set email alerts
|

Decreasing Substance use Risk among African American Youth: Parent-based Mechanisms of Change

Abstract: African American couples (N = 139; 67.7% married; with children between the ages of 9 and 14) were randomly assigned to (a) a culturally sensitive, couple- and parenting-focused program designed to prevent stress-spillover (n = 70) or (b) an information-only control condition in which couples received self-help materials (n = 69). Eight months after baseline, youth whose parents participated in the program, compared with control youth, reported increased parental monitoring, positive racial socialization, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…Previous analyses using data from Wave 1 (W1) and Wave 2 (W2) indicated that, approximately 9 months after baseline, ProSAAF couples’ communication, satisfaction, and confidence were greater than those of couples in the control condition (Barton et al, 2017). In addition, among an initial subset of 139 families (50% intervention), ProSAAF families reported better parenting and youth outcomes than did those in the control condition (Beach et al, 2016). The current study builds on these findings by examining: (a) program effects on rates of change in couple, coparenting, and parenting processes over a 17-month period, and (b) mechanisms of program effects through path models using three waves of data that control for baseline levels.…”
Section: The Protecting Strong African American Families Programmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous analyses using data from Wave 1 (W1) and Wave 2 (W2) indicated that, approximately 9 months after baseline, ProSAAF couples’ communication, satisfaction, and confidence were greater than those of couples in the control condition (Barton et al, 2017). In addition, among an initial subset of 139 families (50% intervention), ProSAAF families reported better parenting and youth outcomes than did those in the control condition (Beach et al, 2016). The current study builds on these findings by examining: (a) program effects on rates of change in couple, coparenting, and parenting processes over a 17-month period, and (b) mechanisms of program effects through path models using three waves of data that control for baseline levels.…”
Section: The Protecting Strong African American Families Programmentioning
confidence: 97%
“…In this article, we summarize the conceptualization of the program and present results from a randomized controlled trial with rural African American couples. Building on previous studies supporting ProSAAF’s short-term impact (Barton et al, 2017; Beach et al, 2016), the current study uses three waves of data spanning 17 months to investigate the program’s impact on rates of change in couple, coparenting, and parenting interactions, as well as the mechanisms through which these effects occur.…”
mentioning
confidence: 99%
“…Prevention research on RES and risk‐taking behavior supports these messages buffering adolescents from engaging in risk behaviors, particularly when prevention programming targets RES, specifically, and in conjunction with universal supportive parenting practices (e.g., Brody et al., ). These programs focus on teaching parents to use nurturant‐involved parenting along with high levels of monitoring and control, adaptive RES strategies, skills to communicate about sex and substance use, and guidelines for establishing clear expectations about substance use (Beach et al., ; Brody, Kogan, Chen, & Murry, ) . Outcome studies have shown that these programs are associated with lower rates of initiation in high‐risk behaviors, including lower levels of substance initiation and use, lower sexual risk taking, and greater declines in conduct problems (Beach et al., ; Brody, Chen, Kogan, Murry, & Brown, ; Brody et al., ).…”
Section: Summary and Integrationmentioning
confidence: 99%
“…These programs focus on teaching parents to use nurturant‐involved parenting along with high levels of monitoring and control, adaptive RES strategies, skills to communicate about sex and substance use, and guidelines for establishing clear expectations about substance use (Beach et al., ; Brody, Kogan, Chen, & Murry, ) . Outcome studies have shown that these programs are associated with lower rates of initiation in high‐risk behaviors, including lower levels of substance initiation and use, lower sexual risk taking, and greater declines in conduct problems (Beach et al., ; Brody, Chen, Kogan, Murry, & Brown, ; Brody et al., ). The convergence of RES messages with communication about sex and alcohol use likely function to specifically protect non‐White youth in successfully navigating adolescence, but few studies of RES messages have examined how these messages may overlap and across all racial/ethnic groups.…”
Section: Summary and Integrationmentioning
confidence: 99%
“…Of the four themes, cultural socialization, which is characterized by teaching youth about their racial or ethnic heritage and history, promoting cultural customs and traditions, and promoting racial or ethnic pride, has been noted to be one of the more salient components of ethnic-racial socialization ( Hughes et al, 2006 ; Priest et al, 2014 ). Cultural socialization is also generally viewed as adaptive, as it is associated with better health and psychological outcomes among minority youth ( Beach et al, 2016 ; Neblett Jr, Terzian, & Harriott, 2010 ), including decreased risk for depressive and anxiety symptoms ( Bannon Jr, McKay, Chacko, Rodriguez, & Cavaleri Jr, 2009 ; Neblett et al, 2008 ), and increased self-esteem ( Davis & Stevenson, 2006 ; Hughes, Hagelskamp, Way, & Foust, 2009 ) and racial identity ( Neblett, Smalls, Ford, Nguyen, & Sellers, 2009 ). For example, Davis and Stevenson (2006) found that adolescents who received “high doses” of cultural socialization (operationalized as knowledge and pride related to one's history and culture) reported higher self-esteem.…”
Section: Introductionmentioning
confidence: 99%